Teachers' Perspectives on the Implementation of the Merdeka Curriculum in Elementary Schools - Adelia Putri, Liza; Darwanto, Darwanto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: The implementation of Merdeka Curriculum in elementary schools brings significant changes in learning approaches, assessments, and the role of teachers. The background of this change is based on the need for an education system that is more flexible, student-centered, and able to accommodate the diverse potential of students. Method: The study used the Systematic Literature Review (SLR) method on articles published between 2020 and 2024. The SLR process was conducted in a structured, transparent, and replicable manner to ensure the accuracy and consistency of the literature synthesis. Results: The study results show that most teachers welcome the Merdeka Curriculum because it provides flexibility in designing contextual learning. However, various obstacles have also been identified, such as teachers' limited understanding of the curriculum content, insufficient ongoing training, difficulties in adapting to new learning tools, and limited infrastructure and policy support in some regions. These obstacles highlight the urgent need to strengthen teachers' capacities through training, mentoring, and the provision of adequate resources. Novelty: The uniqueness of this study lies in its methodological contribution, namely the comprehensive application of the Systematic Literature Review method to synthesize literature on teachers' perspectives on the Merdeka Curriculum. This approach is rarely used in similar studies, providing a comprehensive and evidence-based overview that can serve as a reference for policy and learning practices.